A systematic review of the transformative impact of the digital revolution on higher education in South Africa - Mabidi, N. (South African Journal of Higher Education, 2024)
This article investigates the transformative impact of the digital revolution on South African higher education institutions through a Systematic Literature Review. Thus, EBSCOHost, Emerald, Google Scholar, SAGE Journals, ScienceDirect, Springer Link, Elsevier, and Taylor & Francis were used to retrieve and analyse information from scholarly publications such as book chapters, reports, peer-reviewed journal articles, and other publications (n = 17) in South Africa between 2019 and 2023. The research questions of the study aided the discovery of significant themes to explore the transformative impact of the digital revolution on South African higher education institutions. The study found that challenges to embracing digital education in South African higher education institutions include resistance to change, marginalisation of certain socioeconomic groups, poor infrastructure, lack of funding, inadequate Fourth Industrial Revolution tools for instruction, and lack of Fourth Industrial Revolution skills training and development. In contrast, the opportunities include increased student enrolment, Massive Open Online Courses, use of technology to end social exclusion, research and development, and curriculum redesign. The study put forward recommendations that key stakeholders of higher education institutions can use to improve the curriculum in the digital revolution. Prospects for future research were suggested. The study concluded that while various challenges exist for the digital revolution in South African higher education institutions, opportunities can be explored.